2003
DOI: 10.1093/heapol/czg022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the 1997-98 East Asian economic crisis on health and health care in Indonesia

Abstract: This article identifies the effects of the 1997-98 East Asian economic crisis on health care use and health status in Indonesia. The article places the findings in the context of a framework showing the complex cause and effect relationships underlying the effects of economic downturns on health and health care. The results are based on primary analysis of Indonesian household survey data and review of a wide range of sources from the Indonesian government and international organizations. Comparisons are drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 8 publications
4
69
0
2
Order By: Relevance
“…In the descriptive analyses of trends in professional attendance and caesarean section, we used 3-and 4-year groupings of the year of birth, combining 1998 and 1999 into one group to represent the 2 years during which the economic crisis was most severe. 17 For our adjusted regressions, we modelled time as a linear variable (assuming a constant change per year), allowing for changes in the trend at 1991, when the village midwife programme was fully under way, and at 1997, when the economic crisis began.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the descriptive analyses of trends in professional attendance and caesarean section, we used 3-and 4-year groupings of the year of birth, combining 1998 and 1999 into one group to represent the 2 years during which the economic crisis was most severe. 17 For our adjusted regressions, we modelled time as a linear variable (assuming a constant change per year), allowing for changes in the trend at 1991, when the village midwife programme was fully under way, and at 1997, when the economic crisis began.…”
Section: Discussionmentioning
confidence: 99%
“…After the crisis hit the country in 1997, incomes fell, prices of basic goods increased and the government's expenditure on health and education declined. 12,17 The purported effects of the crisis on healthcare use have been contradictory, but there were reports of declining use of government-run health centres and village health posts. 17 However, some strategies to mitigate the effects of the crisis on the health of the poor may have protected the midwife programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three studies focus on economic crises because economic crisis are regularly encountered by organizations and are also very impactful (Cutler et al, 2002;Waters, Saadah, & Pradhan, 2003).…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Economic effects, in consumer side, can be considered as direct effect since it is the result of the shrink in trade volume, employment and the purchasing power. Consumers can also be exposed to psychological effects due to the possibility of decreasing their own income and the general demoralizing climate in market place (Waters, Saadah and Pradhan, 2003). In their study, Zurawicki and Braidot (2005) demonstrated clearly the changing behaviors of consumers to adjust their spending in the parallel of economic crisis.…”
Section: Introductionmentioning
confidence: 99%